Development and Validation of a Teacher Innovation Behavior Assessment Scale (EECI-E): Confirmation by Bifactorial Modeling - Aboufirass, Radouane; Lotfi, Said (Darul Yasin Al Sys, 2025)
This study aimed to develop and validate the Échelle d’Évaluation du Comportement Innovant chez les Enseignants (EECI-E), a scale for evaluating innovation behavior in teachers using bifactor modeling within five Moroccan secondary schools and universities with regulated access. Drawing on Churchill’s model of scale development and measurement theory, the research followed a multi-step process involving item generation, selection, scaling, field testing, and refinement. An initial pool of items was assessed through exploratory factor analysis (EFA) with a sample of 290 teachers recognized for their innovative pedagogical practices across 17 institutions in five Moroccan cities. The construct validity of each emergent factor was subsequently evaluated. The results yielded a 24-item scale comprising four distinct dimensions: Design and Evaluation, Objects, Conditions of Achievement, and Intervention Strategy. These four dimensions accounted for 77.178% of the total variance, with strong internal consistency (Cronbach’s alpha α = 0.961) and high test-retest reliability (r = 0.922). Confirmatory factor analysis supported a bifactor structure, identifying a general factor that captures a teacher’s overall capacity to drive innovative instructional change. Model fit indices indicated satisfactory levels, supporting the robustness of the proposed scale. Despite minor limitations, the EECI-E scale demonstrates strong psychometric properties and can be applied in similar educational contexts to support ongoing quality improvement in teaching innovation.